IMAGINING AND ENABLING THE COLLABORATIVE COMMONS - McGuire, Mark (AoIR Selected Papers of Internet Research, 2015)
The increasing popularity of personal, mobile digital technologies social networks have given rise to what Rainie and Wellman refer to as “networked individualism” (2012). Participants engage with others in multiple networks through the ongoing circulation of content that Jenkins, Ford and Green describe as Spreadable Media (2013). Rifkin documents the development of a “Collaborative Commons” that he believes is taking shape as a result of this connecting and sharing over digital networks (2014). However, the networks that enable this activity can be private or public, and, like the content they carry, they can be open or closed. In this paper, I examine and compare the work of open advocates from the fields of Education and Design to see how the ideas and projects from one area can inform the other, and to discover underlying principles and approaches that can support, strengthen and enlarge the collaborative commons.